Alumina Nanoparticles Enhance the Directional Tensile Properties of Glass/Epoxy Composite. Issue 1 (January 2016) - Rajanish, M; Nanjundaradhya, N V; Sharma, Ramesh S; Shivananda, H K
In this paper, diglycidyl ether of bisphenol A (DGEBA) / triethylene tetramine (TETA) system is used as the starting epoxy matrix and alumina nanoparticles at various concentrations (0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% and 1.0wt%) are employed to modify the epoxy matrix. The UD (unidirectional) glass fibres are used along with the unmodified and modified epoxy resins for fabricating the composite laminates by hand layup process followed by vacuum bagging. The tensile properties of the composite such as tensile strength and tensile modulus are investigated along the longitudinal, transverse direction and also at 45° orientation of fibres using a universal testing machine. From the results, it is found that tensile modulus of the composites was influenced much by the addition nano-fillers while the tensile strength was found to be less altered. Also, the present study showed that nano-modified composites exhibit significantly improved tensile properties along the transverse direction while the properties along the longitudinal direction were not affected much by the nano-fillers due to the dominating effect of the fibres. The maximum enhancement of tensile modulus and tensile strength was found to be 8.85% and 3.72% in the composite having 0.6wt% of alumina nanoparticles in the transverse direction. Further addition of nanoparticles decreased the properties, which were explained with the concept of agglomerations formed by the nanoparticles in the matrix which weakens the mechanical properties. The graphs are employed to explain the results. Hence, to obtain a best possible design, the properties of the fibre reinforced nano-composite laminate at different angles are to be considered as continuous variables in a design process.